Ageing as "early-life inertia": Disentangling life-history trade-offs along a lifetime of an individual. Issue 5 (1st October 2021) - Carlsson, Hanne; Ivimey-Cook, Edward; Duxbury, Elizabeth M. L.; Edden, Nathan; Sales, Kris; Maklakov, Alexei A.
Abstract: The theory that ageing evolves because of competitive resource allocation between the soma and the germline has been challenged by studies showing that somatic maintenance can be improved without impairing reproduction. However, it has been suggested that cost-free improvement in somatic maintenance is possible only under a narrow range of benign conditions. Here, we show that experimental downregulation of insulin/IGF-1 signaling (IIS) in C. elegans nematodes, a robustly reproducible life span- and health span-extending treatment, reduces fitness in a complex variable environment when initiated during development but does not reduce fitness when initiated in adulthood. Thus, our results show that the costs and benefits of reduced IIS can be uncoupled when organisms inhabit variable environments, and, therefore, do not provide support for the resource allocation theory. Our findings support the theory that the force of natural selection on gene expression in evolutionarily conserved signaling pathways that shape life-history traits declines after the onset of reproduction resulting in organismal senescence.